Perkembangan Anak Pra Sekolah di Tinjau dari Status Gizi - Komariah, Nurul; Murdiningsih, Murdiningsih; Hindun, Siti; Wahyuni, Sari (Poltekkes Kemenkes Padang, 2023)
Background: The prevalence of developmental delays in children is 12-16% in America and 13-18% in Indonesia. The ability to attend school is low and the economy is limited in adulthood. A 20% income deficit in adulthood because of loss of potential development. Nutritional status is one of the factors in child development but this is still pros and cons. Objective: To analyze nutritional status with child development. Method: The design used is Cross-sectional. The Study was conducted From September - November 2019.Total Population was 200 children. The research sample was all children attending PAUD in Srijaya Village, Alang-alang Lebar District in 2019 who fulfilled the inclusion and exclusion criteria. TB and BB were measured to assess children's nutritional status and then assessed by the WHO Growth Chart. Child development using KPSP. Bivariate data analysis with Chi-Square. Results: 16.7% obese, 83.3% good nutritional status. Doubtful child development is 36.7%, and appropriate child development is 63.3%. nutritional status was not related to child development (p=0.47). The RP results show that children with good nutritional status have a 10.826x chance that their development is appropriate compared to obese children. Conclusion: Nutritional status is not related to child development. Suggestion: Parents to provide democratic parenting, stimulate and good nutrition to children. Health Workers to routine carry out early detection of the development of toddlers.